Vaginal microbiocenosis and citocine genes polymorphism as the female health marker (literature review) - V N Prilepskaya; A B Letunovskaya; A E Donnykov (IP Berlin A.V., 2015)
The review is devoted to modern notions of vaginal microbiocenosis and the use of hormonal contraception as well as modern methods of researching and assessing vaginal microbiocenosis.